GENAI DALAM PENDIDIKAN TINGGI: DAPATKAH KESIAPAN DIGITAL MENINGKATKAN KETAHANAN AKADEMIK? - Erlyn Ayu Natali; Moch. Hamzah Rofiulloh; Nadya Eka Samudra Pratiwi; Yuta Afiyanto Ramandani; Achmad Virgi Ardian Febrianto; Irena Yolanita Maureen (EDUPEDIA, 2025)
This study aims to examine the relationship between digital readiness, perceived usefulness of Generative Artificial Intelligence (GenAI), and academic resilience among university students in the digital learning era. The research involved 45 undergraduate students from Universitas Negeri Surabaya as respondents, selected to represent learners who actively engage in technology-supported academic activities. Using a quantitative approach, data were collected through a structured questionnaire measuring digital readiness, perceived usefulness of GenAI, and academic resilience, adapted from validated instruments in previous studies. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to evaluate both the measurement and structural models. The results show that digital readiness has a significant positive effect on academic resilience, indicating that students with higher digital preparedness tend to possess better adaptability and persistence when facing academic challenges. Digital readiness also significantly influences perceived usefulness of GenAI, suggesting that students who are more digitally prepared are more likely to view GenAI as beneficial for learning. However, perceived usefulness of GenAI does not significantly affect academic resilience and does not mediate the relationship between digital readiness and academic resilience. These findings underscore that digital readiness serves as a direct and dominant predictor of academic resilience, while the perceived usefulness of GenAI has not yet functioned as a psychological mechanism that strengthens students’ adaptive capacity. The study highlights the importance of improving students’ digital competencies to foster resilience in technology-driven learning environments.